Dietary Carotenoid Intakes and Prostate Cancer Risk: A Case-Control Study from Vietnam - Van Hoang, D.; Pham, N.; Lee, Andy; Tran, D.; Binns, Colin (MDPI Publishing, 2018)
The incidence of prostate cancer has increased in Vietnam, but there have been few studies of the risk factors associated with this change. This retrospective case-control study investigated the relation of the intake of carotenoids and their food sources to prostate cancer risk. A sample of 652 participants (244 incident prostate cancer patients, aged 64-75 years, and 408 age frequency-matched controls) were recruited in Ho Chi Minh City during 2013-2015. The habitual diet was ascertained with a validated food-frequency questionnaire, and other factors including demographic and lifestyle characteristics were assessed via face-to-face interviews by trained nurses. Multivariate-adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression models. The risk of prostate cancer decreased with increasing intakes of lycopene, tomatoes, and carrots; the respective ORs (95% CIs) were 0.46 (0.27, 0.77), 0.39 (0.23, 0.66), and 0.35 (0.21, 0.58), when comparing the highest with the lowest tertile of intake (p for trend < 0.01). No statistically significant associations were found for the intake of a-carotene, ß-carotene, ß-cryptoxanthin, lutein, zeaxanthin, and major food sources of carotenoids. In conclusion, Vietnamese men with a higher intake of lycopene, tomatoes, and carrots may have a lower risk of prostate cancer. However, large prospective studies are needed in this population to confirm this finding.